DEX Methodology: Three Decades of Qualitative Multi-Attribute Modeling - Bohanec, Marko; Žnidaršič, Martin; Rajkovič, Vladislav; Bratko, Ivan; Zupan, Blaž (Informatica)
DEX Methodology: Three Decades of Qualitative Multi-Attribute Modeling